Non-genetic factors influencing growth and fleece traits in Afrino sheep - Snyman, M.A.; Erasmus, G.J.; Wyk, J.B. van (1995)
Data, consisiting of 4235 lamb records, obtained from the Foundation Afrino Sheep stud at the Carnarvon Experimental station, were used to investigate factors influencing birth weight, weaning weight, monthly body weight from five to 12 months, body weight at 18 months of age as well as clean fleece weight, as well as clean fleece weight and mean fiber diameter at 16 months of age. Year/season of birth, sex and birth/rearing status of the lamb as well as age of dam and age of lamb were significant (P